Derivation of the arbitrage pricing model (ATP) - Gregoire C., Jorge; Zurita L., Salvador (Estudios de Administración, 1995)
The purpose of this note is to clarify an aspect of linear algebra that appears in the development of Ross 1976's arbitration theory, as presented, for example, in Copeland and Weston 1988.